Secular changes in personality: study on 75‐year‐olds examined in 1976–1977 and 2005–2006. (16th May 2012) - Billstedt, E.; Waern, M.; Duberstein, P.; Marlow, T.; Hellström, T.; Östling, S.; Skoog, I.
<x xml:space="preserve">Abstract</x> Objective In order to study secular changes in personality factors neuroticism and extroversion, representative population samples of non‐demented 75‐year‐olds underwent psychiatric examinations in 1976–1977 (total n = 223, 138 women, 85 men) and 2005–2006 (total n = 556, 322 women and 234 men). Methods Eysenck Personality Inventory was used at both occasions. Demographic factors (educational level, marital status, having children) were registered. Results Seventy‐five‐year‐olds examined in 2005–2006 had higher values on extroversion and lower values on the Lie scale compared with those examined in 1976–1977. Neuroticism did not differ between the two birth cohorts. Neuroticism scores were higher in women than in men both in 1976–1977 and 2005–2006, and Lie score was higher in women than in men in 2005–2006. Conclusions Our findings suggest that present cohorts of 75‐year‐olds are more extroverted and less prone to respond in a socially desirable manner than those born three decades earlier. Neuroticism levels remained unchanged, suggesting this trait may be less influenced by environmental factors than the other traits studied. Copyright © 2012 John Wiley & Sons, Ltd.